A double plateau and unprecendented circumstellar variable sodium in the transient SN 2011A. Issue Volume 9:Issue S296(2013) (29th January 2014) - de Jaeger, T.; Anderson, J.; Pignata, G.; Hamuy, M.
Abstract: We present optical photometry and spectrosopy of the transient SN 2011A. Our data spans 140 days after discovery including BVRIu'g'r'i'z' photometry and a sequence of 11 spectra. First classified as a type IIn supernova due to the presence of narrow H α emission, this object shows exceptional characteristics. Firstly, the light curve shows a double plateau; a property only before observed in the impostor object SN 1997bs. Secondly SN 2011A has a very low luminosity for a type IIn supernova placing it between the type IIn supernovae and impostor classes in terms of luminosity. Thirdly, SN 2011A shows low velocity and high equivalent width sodium doublet absorption which increases with time and is most likely of circumstellar origin. This evolution is also accompanied by a change of line profile. When the absorption becomes stronger, a P-Cygni profile appears.